Teaching Written Descriptive Text through Gallery Walk Technique - Mardiana Mardiana; Syamsul Bahri Ys; Burhansyah Burhansyah (Research in English and Education Journal, 2020)
This study is intended to find out whether the use of Gallery Walk technique can improve the students’ ability in writing descriptive text or not. This is an experimental research that used one group pretest-posttest design. The population of this study was the tenth grade students of SMA Negeri 5 Banda Aceh. The sample of this study is class X-4 consisting of 25 students selected by using simple random sampling. The instrument of data collection is written test. The result of data analysis showed that the students’ mean score in pretest was 53.24 and the mean score in posttest was 76.8. Moreover, the analysis of t-test showed that tscore ttable or 12.144 1.711 at the level of significance 0.05 with the degree of freedom (df) 24. The most improvement of writing aspects was in content and organization. Other aspects such as grammar, vocabulary and mechanics also improved, but not as much as those two aspects. It means that the use of Gallery Walk technique improved students’ ability in descriptive writing. Thus, the application of Gallery Walk technique can be used to improve the students’ ability in writing descriptive text.